Effect of subdural hemorrhage on term infants development - a prospective study - Ketut Ariawati; Soetjiningsih Soetjiningsih; I. K. Kari (Indonesian Pediatric Society, 2007)
Background Subdural haemorrhage (SDH) is a common problemin infants under 6 months of age and it has a risk to develop intodevelopmental delay.Objective To evaluate adverse effects of SDH on the developmentof term infants.Methods It was a prospective cohort study carried out on infantsbelow six months of age admitted to Sanglah Hospital due toSDH. Control was healthy term infants born in Sanglah Hospital.Mullen Scales test was performed at the age of 6 and 12 months.Multivariate analysis was conducted to examine the relationshipbetween several independent variabels and developmentaloutcome.Results Sixty six infants were enrolled in this study (33 infantswith SDH and 33 infants without SDH), 52 (79%) were maleand 14 (21%) were female. Mean age was 1.53 (SD 0.75) monthsvs 1.70 (SD 0.73) months. The result of Mullen Scales test at theage of 6 and 12 months showed that very low category was higherin infants with the history of SDH than that in control group.Multivariate logistic regression analysis showed that only SDHcorrelated with Gross Motor and Cognitive Scale delay at theage of 6 months and 12 months (Gross motor 6 months: P=0.01;OR 13.07; 95%CI 2.04;83.84; Gross motor 12 months: P=0.00;OR 23.58; 95%CI 2.87;193.84); (Cognitive 6 months: P=0.00;OR 12.11; 95%CI 2.44;59.90; Cognitive 12 months: P=0.00; OR26.67; 95%CI 3.25;218.86).Conclusion Term infants with history of subdural haemorrhageare associated with increased Gross Motor and Cognitive Scaledelay at the age of 6 and 12 months.